Neuroimmune modulatory effects of the NLRP3 inflammasome: the role of sex and living environment in brain affecting conditions - Ciani, Miriam; Rigillo, Giovanna; Bertarini, Beatrice; Benatti, Cristina; Alboni, Silvia; Tascedda, Fabio (Frontiers in Immunology, 2025)
The NLRP3 inflammasome is a master regulator of neuroinflammation, linking systemic perturbations to brain dysfunction and thereby influencing overall brain health. Its sensitivity to biological sex and environmental factors suggests that NLRP3 may act both as a contributor to sex-dependent disease mechanisms and a modifiable therapeutic target for pharmacological and non-pharmacological interventions. In this mini-review, we summarize emerging evidence on sex-specific differences in NLRP3 signaling that may contribute to disparities between males and females in disease incidence, symptomatology, and treatment response. Neuroinflammation-driven disorders, including atherosclerosis, neuropathic pain, substance use, and stress-related syndromes, show how sex influences NLRP3 inflammasome expression and activity with downstream effects on cognition and behavior. We also examine the modulatory influence of environmental factors, with emphasis on social behavior and environmental enrichment, as determinants of NLRP3 dynamics relevant to neurocognitive function and brain health. Overall, the findings suggest that NLRP3 acts as a central hub integrating sex and environmental influences, with broad implications for personalized interventions in brain-related disorders.